Assessment of genetically modified maize GA21 × T25 for food and feed uses, under Regulation (EC) No 1829/2003 (application EFSA‐GMO‐DE‐2016‐137). (27th January 2023) - ; Mullins, Ewen; Bresson, Jean‐Louis; Dalmay, Tamas; Dewhurst, Ian Crawford; Epstein, Michelle M; Firbank, Leslie George; Guerche, Philippe; Hejatko, Jan; Moreno, Francisco Javier; Naegeli, Hanspeter; Nogué, Fabien; et al.
Abstract: Genetically modified maize GA21 × T25 was developed by crossing to combine two single events: GA21 and T25. The GMO Panel previously assessed the two single maize events and did not identify safety concerns. No new data on the single maize events were identified that could lead to modification of the original conclusions on their safety. The molecular characterisation, comparative analysis (agronomic, phenotypic and compositional characteristics) and the outcome of the toxicological, allergenicity and nutritional assessment indicate that the combination of the single maize events and of the newly expressed proteins in maize GA21 × T25 does not give rise to food and feed safety and nutritional concerns. The GMO Panel concludes that maize GA21 × T25, as described in this application, is as safe as its conventional counterpart and the non‐GM reference varieties tested, and no post‐market monitoring of food and feed is considered necessary. In the case of accidental release of viable maize GA21 × T25 grains into the environment, this would not raise environmental safety concerns. The post‐market environmental monitoring plan and reporting intervals are in line with the intended uses of maize GA21 × T25. Post‐market monitoring of food and feed is not considered necessary. The GMO Panel concludes that maize GA21 × T25 is as safe as its conventional counterpart and the non‐GM reference varieties tested, with respect to potential effects on human and animal health and the environment.